(untitled) (Research, Society and Development, 2022)
This work proposes a quantitative and qualitative analysis of the relationship between the blackout that occurred in the Amapá System on November 3, 2020 and its influence on the number of registered cases of COVID-19 in the state of Amapá through the analysis of reports issued by the National Electric System Operator – ONS, articles and news published by the local press and official data published by the government of Amapá. The study seeks to evaluate the impacts on public services, as well as to establish an overview of public health during the event and to verify the risks and vulnerabilities that the current Amapá EPS presents in order to estimate the threats that the interruption of energy supply can cause to the population during a pandemic time.